2018
DOI: 10.1149/2.0081806jes
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Durability of PBI-Based HT-PEM Fuel Cells: Effect of Operating Parameters

Abstract: This work studies the long-term durability of high-temperature polymer electrolyte membrane fuel cells based on acid-doped polybenzimidazole membranes. The primary focus is on acid loss via the evaporation mechanism, which is a major cause of degradation in applications that involve long-term operation. Durability is assessed for 16 identically fabricated membrane electrode assemblies (MEAs), and evaluations are carried out using operating parameters as stressors with gas stoichiometries ranging from 2 to 25, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 42 publications
0
48
0
Order By: Relevance
“…It is not easy to find comparable durability data in the literature, because most durability testing is performed at 160 °C and not at 180 °C, a temperature that was deliberately chosen to accelerate the test. However, we do have other durability measurements at 180 °C from a parallel study in our group . At 200 mA cm −2 and 180 °C and with C2 on both sides and comparable membrane thickness, the decay rate was ca.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not easy to find comparable durability data in the literature, because most durability testing is performed at 160 °C and not at 180 °C, a temperature that was deliberately chosen to accelerate the test. However, we do have other durability measurements at 180 °C from a parallel study in our group . At 200 mA cm −2 and 180 °C and with C2 on both sides and comparable membrane thickness, the decay rate was ca.…”
Section: Resultsmentioning
confidence: 99%
“…Yu et al operated cells at typical operating temperatures of 160 °C and 190 °C with a voltage degradation rate of 4.9 µV h −1 and 60 µV h −1 and an acid loss rate of 7.6 ng cm −2 h −1 and 110.4 ng cm −2 h −1 , respectively. Søndergård et al reported an even stronger temperature effect at higher stoichiometries of hydrogen and air. In this work, the fuel cell operational temperature of 180 °C was selected as a stressor to the long term durability test of HT‐PEMFCs with varied gas diffusion layer materials.…”
Section: Introductionmentioning
confidence: 99%
“…The equilibrium acid doping level of the PBI‐CLI and PBI‐CLII was significantly lower than that of the membrane based on linear PBI, and nearly 200 h were required to reach equilibrium at room temperature. Increasing area specific resistance is mainly correlated to acid loss from the membrane , and the higher degradation rates of fuel cells based on PBI‐CLI and PBI‐CLII is likely a consequence of the rigid cross‐linked structure promoting acid leaching. The N ‐functionalization of the benzimidazole is also likely weakening the polymer‐phosphoric acid interaction, which could further promote the acid leaching.…”
Section: Resultsmentioning
confidence: 99%
“…However, the phosphoric acid tend to redistribute , or leach out during operation, which represents a predominating degradation mode of the fuel cell performance. This is particularly severe at high current loads, at high gas flow rates and at temperature in the higher end of the operating temperature window . Introduction of an inorganic phase, such as titanyl sulfate , titania , or mesoporous silica , , in the membrane matrix may stabilize the performance and extend the lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, the reactant gases transfer more easily and uniformly to the reaction zones; therefore, the intensity of the electrochemical reactions is amplified. Cleemann et al [26] investigated the performance of high-temperature polymer electrolyte membrane fuel cells based on acid-doped polybenzimidazole membranes. They found that high temperature enhances performance during drive cycles, and high gas flow rate for cooling increases acid loss.…”
Section: Introductionmentioning
confidence: 99%